COMMUNICATIVEFEATURES OF THE ORALDISCOURSE OF THE TV INTERVIEW - Bermukhambetova, А.А.; Kurmangaliyev, А.А. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
He article presents communication strategies that characterize the oral discourse of the TV host and the interviewee in the genre of TV interviews; describes a set of communication moves used by communication participants to implement their communication tactics and strategies. TV discourse in the genre of TV interviews is considered by us as an interactive process between a TV Communicator, a guest of a TV program, and sometimes a TV audience, which are represented by three systems. These include strategies that are implemented by the following participants in the discourse: 1) telecommunication; 2) guests who are directly involved in the communication process in the Studio.
Keywords: speech strategy; communication techniques; telepictures; a television interview; the participants of the discourse